If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(y + 3) + -3(2y + -6) + -14y = 0 Reorder the terms: -2(3 + y) + -3(2y + -6) + -14y = 0 (3 * -2 + y * -2) + -3(2y + -6) + -14y = 0 (-6 + -2y) + -3(2y + -6) + -14y = 0 Reorder the terms: -6 + -2y + -3(-6 + 2y) + -14y = 0 -6 + -2y + (-6 * -3 + 2y * -3) + -14y = 0 -6 + -2y + (18 + -6y) + -14y = 0 Reorder the terms: -6 + 18 + -2y + -6y + -14y = 0 Combine like terms: -6 + 18 = 12 12 + -2y + -6y + -14y = 0 Combine like terms: -2y + -6y = -8y 12 + -8y + -14y = 0 Combine like terms: -8y + -14y = -22y 12 + -22y = 0 Solving 12 + -22y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -22y = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -22y = 0 + -12 -22y = 0 + -12 Combine like terms: 0 + -12 = -12 -22y = -12 Divide each side by '-22'. y = 0.5454545455 Simplifying y = 0.5454545455
| c=3b+4a-p | | 3(4x+6)-36= | | -1/3+4/5u=-3/2 | | z^2=5 | | 13(t-1)=8t-(8-5t) | | 1/3(5y-2)+1/6(8y+6) | | z^2-5=0 | | 4/7x+5/9 | | 8x+3/4=9x-9/4 | | (x+19)+(3x-22)+x=572 | | n+4=3n+22 | | (x+19)+(22-3x)+x=572 | | 0.80x+0.50(100)=0.40(65) | | 8^5+16w^3/4w | | 5n-17=11+3n | | (x+19)+(22-3x)=x | | 2x+3(2x-7)=-14 | | 2x+3(2x)-7=-14 | | (x+19)+(22-4x)+x=572 | | .8(.1x+.5)=-.8 | | -5x+6=-2(4y+3) | | p=(2*23)+(2*45) | | -1/2x-5y=6 | | -2[(-3-2)-2(-2+m)]=-3m-16-2 | | -2x/3-2=-7 | | 68x=95.2 | | (x+400000)+x=600000000 | | 9(x-5)-2=-47 | | (9/4)x+1 | | -x=56 | | x+(x+32)+(2x-33)=751 | | 9(t-5)+5t=7(2t+4)-12 |